AN ANALYSIS OF TEACHERS’ QUESTIONING STRATEGIES IN ELT (ENGLISH LANGUAGE TEACHING) THE CLASSROOM INTERACTION AT ELEVENTH GRADE SMA MUHAMMADIYAH 1 UNISMUH MAKASSAR - Ayu Erianti; Erwin Akib; Farisha Andi Baso (Universitas Muhammadiyah Makassar, 2018)
This research deals with teacher questions in senior high school English classroom. The study was conducted to answers three of problem statement. The study was conducted at SMA Muhammadiyah 1 UNISMUH Makassar with the descriptive qualitative method. The study was carried out by observing, interview and taking video recordings of 1 English teacher and 15 students. The researcher takes 2 class in one meeting consist of 90 minutes each class. The result showed that procedural (13%), display (74%) and referential (13%) questions were found in the type of teacher questioning strategies used. However, the reason why teacher used the types of the question is according to the function of the question type. Then the effect of the question to the students based on 6 questions that researcher asked. 60% students agree with the Q1 and 40% disagree. For the Q2 100% students agree with the question that researcher ask and also the Q3 100% students agree with the question. While for Q4 60% students agree and 40% of them disagree. 40% agree and 60% disagree to Q5 and 80% agree and 20% disagree for the Q6.